Design, synthesis, kinetic, molecular dynamics, and hypoglycemic effect characterization of new and potential selective benzimidazole derivatives as Protein Tyrosine Phosphatase 1B inhibitors. (15th October 2021) - Campos-Almazán, Mara Ibeth; Flores-Ramos, Miguel; Hernández-Campos, Alicia; Castillo, Rafael; Sierra-Campos, Erick; Torgeson, Kristiane; Peti, Wolfgang; Valdez-Solana, Mónica; Oria-Hernández, Jesús; Méndez, Sara T.; Castillo-Villanueva, Adriana; Jiménez-de Jesús, Hugo; et al.
Graphical abstract: Highlights: Four new and potential selective benzimidazole derivates as PTP1B inhibitors are reported. Compounds show a complete mixed type of inhibition. Inhibitors show potential selectivity against other phosphatases such as its closest homologous TCPTP, SHP-1, SHP-2 and CDC25B. Compounds show hypoglycemic effect under physiological conditions of glucose metabolism. Abstract: Protein-tyrosine phosphatase 1B (PTP1B) is a negative regulator of insulin signaling pathway and has been validated as a therapeutic target for type 2 diabetes. A wide variety of scaffolds have been included in the structure of PTP1B inhibitors, one of them is the benzimidazole nucleus. Here, we report the design and synthesis of a new series of di- and tri- substituted benzimidazole derivatives including their kinetic and structural characterization as PTP1B inhibitors and hypoglycemic activity. Results show that compounds 43, 44, 45, and 46 are complete mixed type inhibitors with a Ki of 12.6 μM for the most potent (46 ). SAR type analysis indicates that a chloro substituent at position 6(5), a β-naphthyloxy at position 5(6), and a p -benzoic acid attached to the linker 2-thioacetamido at position 2 of the benzimidazole nucleus, was the best combination for PTP1B inhibition and hypoglycemic activity. In addition, molecular dynamics studies suggest that these compounds could be potential selective inhibitors from other PTPs such as its closest homologous TCPTP, SHP-1, SHP-2 and CDC25B. Therefore, the compounds reported here are good hits that provide structural, kinetic, and biological information that can be used to develop novel and selective PTP1B inhibitors based on benzimidazole scaffold.